Landscaponics creating a sustainable community in Bistekville 35 through urban agriculture - Paderna, Frances Patricia B. (College of Architecture, University of the Philippines Diliman, 2019)
Bistekville 35 is a new socialized housing development proposed by the local government unit of Quezon City. Bistekville 35 will be a redevelopment of an informal settlement area and shall be located in a depressed area within San Agustin, Novaliches. Although Bistekville 35 will be great opportunity for informal settlers to be provided secure homes, the problem arises when it comes to the monthly amortization required to stay in the area. Dwellers are discouraged due to the high amortization and limited economic opportunities surrounding the area. Yes, housing is provided but the ability to pay the monthly amortization to stay in this area is nonexistent. Hydroponics farming can be the future of farming. It has been around since the Aztecs but only in recent years has it gain traction for its widespread benefits it terms of cultivation. Hydroponics means that plants are grown not through soil farming but they are grown through water and nutrients rich solutions. Studies show that hydroponics yield much faster and can be harvested easier than soil farming. It also helps plants grow in areas wherein they normally cannot survive. This research focuses on the use of urban agriculture, specifically hydroponics farming, as a strategy to make the area sustainable. Through the implementation of hydroponics systems, livelihood opportunities can be created and the quality of life in the area can be improved.